Coleta seletiva solidária: uma análise das melhores práticas desenvolvidas em órgãos federais em Uberlândia (MG) - Reis, Sarentaty Inês Karoline Santana dos (2018)
Waste disposal and destination have become a challenge to the statewho, with the public policies support, try to ensure that such process will happen in a proper manner. With the goal of setting an example to the institutions and to the society, the Decree nr 5940/2006, which precedes the National Solid Waste Policy, imposed the sorting of the recyclable waste disposed by the agencies and entities of the federal public administration, either direct or indirect, at the point of origin, and its destination to the pickers’ associations and cooperatives for recyclable material. Under such context, this work aims to analyze, in the light of the Public Policies Cycle, which practices related to the solidary waste recycling are adopted at the federal public agencies located in Uberlandia (MG). Methodologically speaking, a multicase study was developed with support of qualitative data, obtained in deep interviews, with further content analysis. In order to complement the frame was obtained through documentary research, participant observation, literature review, semi-structured interviews, institutional newspapers and inquiries to the pertinent law. The results indicate that different situations exist on the analyzed agencies that the three agencies handle differently the Solidary Selective Collection and are going through or have gone through difficulties to provide a proper destination or disposal to their solid waste. Given the presented context, and considering the Public Policy Cycle seen along the literature review, the policy was implemented in the case of the Decree. However, the next step, which is the evaluation of the action and potential correction was not. That being so, it is believed that such policy should be evaluated to discover the main difficulties faced when adopting said public policy. This research produced as technological products a diagnosis of the selective waste collection by federal public agencies in Uberlandia, which can be replicated to further environments, and a proposal for a manual that might help the public agencies with the step-by-step to adopt the Solidary Waste Recycling.